From trepidant abasia to motor network failure - gait disorders as a consequence of subcortical vascular encephalopathy (SVE): review of historical and contemporary concepts - Bäzner, Hansjörg; Hennerici, Michael G. (Journal of the neurological sciences, 2005)
Gait disorders in progressive subcortical vascular encephalopathy (SVE) and their impact on the burden of disability in the growing elderly population are underrepresented in medical scientific literature. The absence of a clear framework for the diagnosis and classification for gait disorders on the basis of SVE has multiple reasons: (1) neither movement disorder specialists nor stroke specialists are truly familiar with this topic and feel responsible for its treatment, (2) the existing terminology lacks a clear concept and a consistent classification, and (3) only in recent years have large prospective trials started to address the natural course of SVE. This article reviews the classical descriptions of gait disturbances with preferential view to our present concept of SVE, and comments on historical and current nosology of gait disorders aiming to propose for a new classification.
Available online: 19 December 2004
Gesehen am 13.05.2022